Bracon sp. (Hymenoptera: Braconidae) parasitoid the Etiella Zinckenella in Panama - Santos-Murgas, Alonso (2024)
This article reports the first record of the parasitoid wasp Bracon sp. (Hymenoptera: Braconidae) that attacks the larvae of Etiella zinckenella (Treitschke, 1832) (Lepidoptera: Pyralidae), a Cajanus cajan (pigeon pea) pest that causes significant damage to seeds. This event was observed in plantations located in Altos de Pacora, Cerro Azul, Panama. The parasitoid could be used in insect biological control programs to combat this pest.